Perancangan Interior Gedung Konser Musik di Samarinda - Hedy C. Indrani, Natalia Manampiring (Intra, 2013)
Music is one of inseparable part in human life. In order to fulfill the needs, many fancy concert buildings are built worldwide, and sort to be an icon of the country which often being visited by foreigner or tourist. Samarinda is one of developing city in Indonesia which often held musik concerts. But with the limitness of the building, the musik concerts is often held outdoor and seems not optimal in acoustic perspective. Applied qualitative method is one of the method to be used for analyze these concert buildings. In this scheme, philosophy aspect of Dayaks culture is applied to promote Samarindas local culture itself and be a special icon for the city. Acoustic calibrating is also done in this building scheme to support its vision as an optimal musik concert place especially in audiovisual aspect.